The Effect of Padlet in Collaborative Learning of â€œKurikulum Merdekaâ€ to Improve Studentsâ€™ Writing Ability in Recount Text - Widia Listianingsih; Arso Setyaji; Ririn Ambarini (ETERNAL (English Teaching Journal), 2023)
On the Learning Achievement (known as â€œCapaian Pembelajaranâ€) of â€œKurikulum Merdekaâ€, students are expected to be able to develop their skill in writing a variety of texts, including recount texts, as one of the competencies that they are expected to master. Writing is one of the competencies that students are required to master. In point of fact, the students face a wide variety of challenges when it comes to writing, including boredom, no relevant method, unenthusiastic, low confidence, old teaching media, and teaching monotonous. To give interesting media in teaching writing, the researchers use Padlet as learning media, because no teachers have used it yet, especially at this school. A quantitative methodology was used in the design of this research. Students in the tenth grade of TPFL 2 at SMK Negeri 7 Semarang were the focus of this particular piece of research. The Pre-Test, the Post-Test, and a questionnaire were the instruments that were utilized in this research. IBM SPSS 29 was used to perform the analysis, and it was also used to process the data. It is possible to draw the following conclusion from the findings: the implementation of Padlet media in the classroom may result in increased student participation and classroom collaboration. The students' writing abilities are significantly improved when they are taught writing through the use of Padlet on recount text. The results of this study have important implications for researchers, particularly those whose interests lie in the fields of education and language, as well as for English teachers as fundamental data for the enhancement of instructional media.